You are on page 1of 3

# ON THE k-TH PART SEQUENCE OF A POSITIVE INTEGER

*

Liu Hongyan Department of Applied Mathematics, Xi’an University of Technology Xi’an, Shaanxi, P.R.China

Abstract.

For any positive integer n, let u(n) and v(n) denote the inferior and superior k-th part of n respectively. That is, u(n) denotes the largest k-th less than or equal to n, and v(n) denotes the smallest k-th greater than or equal to n. In this paper, we study the properties of the sequences {u(n)} and {v(n)}, and give two interesting asymptotic formulas.

1. Introduction For any positive integer n, let u(n) and v(n) denote the inferior and superior k-th part of n respectively. That is, u(n) denotes the largest k-th less than or equal to n, and v(n) denotes the smallest k-th greater than or equal to n. For example, if k = 3, we have u(1) = 1, u(2) = 1, u(3) = 1, u(4) = 1, u(5) = 1, u(6) = 1, u(7) = 1, u(8) = 8, · · · . v(1) = 1, v(2) = 8, v(3) = 8, v(4) = 8, v(5) = 8, v(6) = 8, v(7) = 8, v(8) = 8, v(9) = 27, · · · . In problem 40 and 41 of [1], Professor F.Smarandach asked us to study the properties of the sequences {u(n)} and {v(n)} while k = 2 and k = 3. In this paper, we use the elementary methods to study the properties of these sequences for general k ≥ 2, and give two interesting asymptotic formulas. That is, we shall prove the following: Theorem 1. Let k ≥ 2 be any positive integer, for any real number x > 1, we have the asymptotic formula x Ωt (u(n)) = k t x ln ln x + k t (At − ln k)x + O , ln x
n≤x r t t t where Ωt (n) = α1 + α2 + · · · + αr , t ≥ 0 is an integer, if n =

pαi , At is a i
i=1

constant.

For the superior k-th part sequence {v(n)} of n, we can also get similar result. Theorem 2. Let k ≥ 2 be any positive integer, for any real number x > 1, we have the asymptotic formula x . Ωt (v(n)) = k t x ln ln x + k t (At − ln k)x + O ln x
n≤x

Key words and phrases. Inferior and superior k-th part; Mean value; Asymptotic formula. * This work is supported by the N.S.F.(10271093) and the P.S.F. of P.R.China. Typeset by AMS-TEX 1

2

LIU HONGYAN

2. Proof of the Theorems In this section, we shall complete the proof of the Theorems. First we prove Theorem 1. For any real number x > 1, let M be a ﬁxed positive integer such that (1) M k ≤ x < (M + 1)k .

Then from the deﬁnition of u(n) we have
M

Ωt (u(n)) =
n≤x M −1 l=1 (l−1)k ≤n<lk

Ωt (u(n)) +
M k ≤n≤x

Ωt (u(n))

=
l=1 lk ≤n<(l+1)k M −1

Ωt (lk ) +
M k ≤n≤x

Ωt (M k ) 
M k ≤n≤(M +1)k

 Ωt (M )

=
l=1

klk−1 +

k(k − 1) k−2 l + · · · + 1 k t Ωt (l) + O  2

(2)
M

= k t+1
l=1

lk−1 Ωt (l) + O M k−1 ln M .

Note that (see reference [3]) (3)
n≤x

Ωt (n) = x ln ln x + At x + O

x , ln x

where At is a constant involving t. Let Bt (y) =
m≤y

Ωt (m), by Abel’s identity (see

Theorem 4.2 of [2]) and (3) we have
M

lk−1 Ωt (l) = M k−1 Bt (M ) − (k − 1)
l=1 2

M

y k−2 Bt (y)dy y k−2 (y ln ln y + At y) dy + O Mk ln M

= M k−1 (M ln ln M + At M ) − (k − 1)
2

M

= M k ln ln M + At M k − (k − 1)
2

M

y k−1 ln ln y + At y k−1 dy + O Mk ln M

Mk ln M

k−1 = M k ln ln M + At M k − M k ln ln M + At M k + O k (4) 1 Mk 1 . = M k ln ln M + At M k + O k k ln M Applying (2) and (4) we obtain the asymptotic formula (5)
n≤x

Ωt (u(n)) = k t M k ln ln M + k t At M k + O

Mk ln M

,

ON THE k-TH PART SEQUENCE OF A POSITIVE INTEGER*

3

where At is a constant. On the other hand, from (1) we have the estimates (6) 0 ≤ x − M k < (M + 1)k − M k = kM k−1 + and (7) ln k + ln ln M ≤ ln ln x < ln k + ln ln(M + 1) ≤ ln k + ln ln M + O x− k .
1

k(k − 1) k−2 M + ··· + 1 2

x

k−1 k

Now combining (5), (6) and (7) we immediately get the asymptotic formula Ωt (u(n)) = k t x ln ln x + k t (At − ln k) x + O
n≤x

x . ln x

This proves Theorem 1. Using the methods of proving Theorem 1, we can also prove Theorem 2. This completes the proof of the Theorems . References
1. F. Smarandache, Only problems, not Solutions, Xiquan Publ. House, Chicago, 1993, pp. 34-35. 2. Tom M. Apostol, Introduction to Analytic Number Theory, Springer-Verlag, New York, 1976. 3. R.L.Duncan., A class of additive arithmetical functions, Amer.Math.Monthly 69 (1962), 3436. 4. “Smarandache Sequences” at http://www.gallup.unm.edu/˜smarandache/snaqint.txt. 5. “Smarandache Sequences” at http://www.gallup.unm.edu/˜smarandache/snaqint2.txt. 6. “Smarandache Sequences” at http://www.gallup.unm.edu/˜smarandache/snaqint3.txt.